DEVELOPMENT MODEL OF MEDICAL TOURISM VILLAGE CONCEPT TRI HITA KARANA IN LEMUKIH VILLAGE, SAWAN SUB-DISTRICT, BULELENG REGENCY - Yudi Aryawan, kadek (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
This research plays a crucial role in supporting the direction of policies and programs of the Bali Provincial Government, known as "Nangun Sat Kerthi Loka Bali." The absence of a guideline scheme that can be used as an indicator for determining medical tourism villages based on the Tri Hita Karana concept is a challenge in its operationalization. This study aims to: (1) Design a development model for medical tourism villages based on the Tri Hita Karana concept, (2) Involve higher education personnel in participating and contributing to the central and regional governments in improving the health and economy of communities in the post-COVID-19 pandemic era at the village level through research and development, (3) Foster the potential and destinations of villages, (4) Promote micro, small, and medium-sized enterprises (UMKM) and community-owned businesses through the dissemination of research results from the village. The research results indicate that the government's role in managing tourism resources is dominant. However, in line with the principles of clean, healthy, and sustainable governance, the government's role is expected to be that of a facilitator, providing a more significant role and benefits to the community. his shows that the development of medical tourism based on the Tri Hita Karana concept has not been well realized in this area. Local communities, especially those in Lemukih Village, need to be involved in designing the tourism model that will be developed.